Dominant economic sectors in Kulonprogo, Gunungkidul, and Bantul Regencies in Yogyakarta Special Province - Nur Feriyanto (Economic Journal of Emerging Markets, 2015)
The Special District of Yogyakarta (DIY) subdivided into four regencies and one city has targeted economic growth in Regional Medium Term Development Plan DIY 2012-2017. This research aims to analyze some dominant economic sectors from Regencies of Kulonprogo, Gunungkidul and Bantul in achieving the target of economic growth in the year of 2015-2017. The result of the research showed the economic sectors in Kulonprogo Regency have been dominated by sectors in Agriculture, Services, Trade, hotel and restaurant and Manufacturing industries. In Gunungkidul, it was dominated by Agriculture, Trade, hotel and restaurant, Service, Manufacturing industries and Construction. Meanwhile, in Bantul Regency it was dominated by Agriculture, Trade, hotel and restaurant, Manufacturing industries, Services and Construction.